Clinico-hematological study of leukemias in a hospital-based setup - Roy, Sneha; Nath, Sourav; Goswami, Rashmi Rekha; Sheikh, S. A. (International Journal of Research in Medical Sciences, 2021)
Background: Leukemia, the malignant proliferation of hematopoietic cells, accounts for a major portion of cancer globally. Types of leukemia are necessary for effective therapy as prognosis, and survival rates are different for each type of leukemia. The objective of the study was to know the relative incidence of leukemia in Silchar Medical College and Hospital, Assam. This study also aims to know the clinical manifestations of leukemia and their hematological correlation. Methods: It was a retrospective study of 60 patients carried out in the Department of Pathology in SMCH, Assam, over a period of 2 years from April 2019 to March 2021. Diagnosis was based on peripheral blood count, peripheral blood smear and bone marrow examination for morphology, along with cytochemistry study whenever required. Results: In this study, acute leukemia was more prevalent than chronic leukemia. The most common form was CML followed by AML, ALL and then CLL. Male predominance was observed in this study with male: female ratio = 1.7:1. Conclusions: In our study, Acute leukemia was more prevalent than chronic leukemia. Leukemia affected male more than female. In this study, the frequency of AML is more than that of ALL but number of cases of CML exceeds that of AML.